Neck muscle strength training in the risk management of concussion in contact sports: critical appraisal of application to practice - Gilchrist, I.; Storr, M.; Chapman, E.; Pelland, L. (Journal of Athletic Enhancement, 2015)
Background: Neck strength training has been advocated as a player-specific modifiable factor in the risk management for concussion in contact sports. A scoping review of the literature was undertaken to address two specific aims. The first was to identify and critically appraise the level and quality of evidence relating neck strength and resistance training to concussion incidence and risk in contact sports. The second was to compare and contrast the effectiveness of resistance neck strengthening programs and to evaluate effects of increased strength in attenuating the postimpact kinematics of the head, a proxy measure of concussion risk.